Comparative and Individual Perspectives on Mother–Infant Interactions with People and Objects among South Koreans, Korean Americans, and European Americans. (3rd April 2019) - Bornstein, Marc H.; Cote, Linda R.; Kwak, Keumjoo
Abstract : Comparative and individual acculturation of mother and infant person‐directed and object‐directed behaviors and interactions were investigated among 183 South Korean, Korean American, and European American mothers and their 5½‐month‐old infants. We analyzed and compared mean levels in mothers' and infants' person‐ and object‐directed behaviors and partner responsiveness and initiation of these behaviors in dyads in the three cultural groups. Among Korean American dyads, we also analyzed individual‐level variation in the acculturation of these behaviors and interactions. This study reveals how contrasting South Korean and European American cultural values are embedded and manifested in early mother–infant interactions and how cultural values from South Korean origin and European American destination cultures are interwoven in Korean American mother–infant interactions.